Now I think I should use my initial value, so 75=300+e^c => -225=e^c => 225=-e^c , and take logs of both sides to get ln(225)=-c
Next I should plug -ln(225) for c in the equation ln(y-300)=.4t+c, giving me ln(y-300)=.4t-ln(225) right? Or and I doing something wrong?
I added the log from the right to the left, and using property of logs combined them to a quotient, but the answer after simplification was wrong, so I must be missing something.
225=-e^c , and take logs of both sides to get ln(225)=-c <----NO
if 225 = e^(-c) then -c = ln 225
y=300+e^(.4t+c). y=300+e^(.4t)e^c. y=300-225e^(.4t)
i put e^c = -225
ah i see
any more doubts ? all clear ?
I think so, I am not so quick, I will work it out!
Ah, there really isn't any working out to do because e^c is a constant and its all in terms of y. So simple, thanks again.